2015
DOI: 10.1007/s11276-015-1002-4
|View full text |Cite
|
Sign up to set email alerts
|

Interference mitigation in wireless mesh networks through radio co-location aware conflict graphs

Abstract: Abstract-Wireless Mesh Networks (WMNs) have evolved into a wireless communication technology of immense interest. But technological advancements in WMNs have inadvertently spawned a plethora of network performance bottlenecks, caused primarily by the rise in prevalent interference. Conflict Graphs are indispensable tools used to theoretically represent and estimate the interference in wireless networks. We propose a generic algorithm to generate conflict graphs which is independent of the underlying interferen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 36 publications
(55 reference statements)
0
25
0
Order By: Relevance
“…For example, in interferenceaware CA schemes, the guiding idea is to lower the TID to reduce the intensity of prevalent interference and make the CA more efficient [4]. However, in a recent study [5], we have demonstrated that although TID does give a measure of the impact of interference, it is inconsistent and unreliable as a CA performance prediction, or interference estimation metric. Thus, we can not, with high confidence, compare two CAs or select the most efficient CA for a given WMN from a set of CA schemes by employing their TID estimates as the sole criterion for performance prediction.…”
Section: Motivation and Related Research Workmentioning
confidence: 98%
See 1 more Smart Citation
“…For example, in interferenceaware CA schemes, the guiding idea is to lower the TID to reduce the intensity of prevalent interference and make the CA more efficient [4]. However, in a recent study [5], we have demonstrated that although TID does give a measure of the impact of interference, it is inconsistent and unreliable as a CA performance prediction, or interference estimation metric. Thus, we can not, with high confidence, compare two CAs or select the most efficient CA for a given WMN from a set of CA schemes by employing their TID estimates as the sole criterion for performance prediction.…”
Section: Motivation and Related Research Workmentioning
confidence: 98%
“…Other CA schemes that we implement are the breadth first traversal approach (BFS) [13], a static maximum clique based algorithm (CLQ) [14] and a maximum independent set based scheme (MIS) [10]. We employ two multi-radio multi-channel conflict graph models (MMCGs) viz., the conventional MMCG (C-MMCG) and the enhanced MMCG (E-MMCG) [5] to implement each of the above CA schemes, except GSCA. C-MMCG represents link conflicts in a traditional fashion and does not take into consideration the impact of radio co-location interference (RCI) in a wireless network.…”
Section: Selection Of Ca Schemesmentioning
confidence: 99%
“…The algorithm suggested in [31,33] is used to generate conflict graphs independently of the underlying interference model. Authors used the notion of radio co-location interference, which is caused and experienced by spatially co-located radios in multiradio multichannel (MRMC) WMNs.…”
Section: Related Workmentioning
confidence: 99%
“…Throughput is computed by first recording the aggregate throughputs for the RWMN for a variety of test cases, and then computing their average to obtain a measure of network capacity. Disrupted flows are those which fail to deliver the complete datafile at its intended destination owing to failures in routing mechanisms caused by high interference in the WMN [13]. Thus, DFC is a measure of the intensity of interference in the network.…”
Section: B Simulation Parametersmentioning
confidence: 99%
“…Thus, we implement a set of graph theoretic CA schemes making use of the enhanced multi-radio multi-channel conflict graph (EMMCG) proposed in [13]. The CA set is diverse in terms of network performance, including CAs of different performance levels which is ideal [4], to radio co-location aware Elevated Interference Zone Mitigation CA (EIZM) which exhibits high network capacity [14].…”
Section: Selection Of Ca Schemesmentioning
confidence: 99%